Peran Digital Marketing Dalam Memediasi Pengaruh Electronic Word Of Mouth, Promosi dan Harga Terhadap Impluse Buying (Studi pada E-commerce Shopee) - Febrina Dian Rahmawati (Journal of Economics and Business Aseanomics (JEBA), 2022)
This study aims to analyze the role of digital marketing, promotion and price on impulse buying through digital marketing as a mediating variable (Study on E-commerce Shopee). The population of this research is Shopee customers. The data analysis method was using Stuctural Equation Modeling (SEM) using SmartPLS version 3.0 software. The results showed that Electronic Word Of Mount, Promotion and Price had a positive and significant effect on Impulse Buying. Digital Marketing mediates Electronic Word Of Mount, Promotion and Pricing on Impulse Buying